External strengthening of RC beams using Gigantochloa Levis (Buluh Beting) fiber reinforced composite plate - Chui, Hong Leng (2018)
Synthetic fiber reinforced polymer (FRP) composite is an efficient method for strengthening of reinforced concrete (RC) externally. Unfortunately, the non-renewable, high cost production and environmental harmful of synthetic fibers had increased public awareness towards this issue and hence inevitable arisen the uses of renewable resources. A research had been conducted to investigate the potential of application of bamboo fiber reinforced composite plate (BFRCP) in external strengthening of RC beam. The bamboo fibers used was Gigantochloa Levis, also known as Buluh Beting which were obtained from Raub, Pahang. Mechanical behaviour of raw and dried bamboo was tested with compression and tensile tests. Besides, the composite plates with 0% and 40% fiber volume were tested for tensile test (ASTM D3039) and flexural test (ASTM D790-03) to identify the mechanical properties. Four-point loading test was conducted to investigate the structural behaviour of RC beams. Based on the result of the mechanical behaviour of bamboo, the dried bamboo showed higher mechanical strength as compared with the raw bamboo. However, the over-dried bamboo will affect the mechanical result. In terms of the composite behaviour, there was an increment of 374.59% of average ultimate tensile strength of fiber reinforced composite as compared to the un-reinforced composite. Whereas, for flexural test, the average ultimate strength of fiber reinforced composite was 11.76 times or 750.60% more than the neat epoxy sample. In terms of structural behavior, it was found that the un-strengthened beam without the shear link in the flexure zone (UNST) has shown a reduction in ultimate load of about 6.72% as compared to the control beam (CB). Whereas, two beams without the shear link in the flexure zone strengthened using BFRCP (ST) had an increment of 9.30% and 10.63% in terms of beam capacity as compared to beam UNST. Besides, both the strengthened beams, ST proven the capability to restore the load carrying capacity of the control beam. In terms of crack pattern, the BFRCP had diverted the cracks from the flexure zone to the edge of the plate for RC beam. Hence, this signifies that BFRCP has potential to be used as an alternative external strengthening material to the synthetic composite plate.